THE EFFECT OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, AND TRUST IN QRIS ON GENERATION Z’S EXPERIENCE IN MSME TRANSACTIONS - Maria Fitriani Fono; Citra Sarasmitha (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze Generation Z's experience in using the Quick Response Code Indonesian Standard (QRIS) for transactions at Micro, Small, and Medium Enterprises (MSMEs), utilizing the Technology Acceptance Model (TAM) framework. This model examines the influence of three independent variables; Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Trust on the QRIS user experience (Y). A quantitative method was employed by distributing questionnaires to 96 Generation Z students from the Faculty of Economics and Business at Universitas Merdeka Malang who actively use QRIS for transactions at MSMEs. The data were analyzed through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS 27. The results indicate that PEOU, PU, and Trust, both simultaneously and partially, have a positive and significant influence on Generation Z's experience in using QRIS. These findings underscore that ease of use, perceived benefits, and especially trust in system security (which has the most dominant influence) are crucial factors in shaping a positive digital transaction experience for Generation Z, while also supporting the transparency of MSME accounting information systems.